ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN PENDANAAN STRUKTUR MODAL EKSTERNAL PADA PERUSAHAAN INDUSTRI MANUFAKTUR DI INDONESIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bagu, Agustin; Karamoy, Herman; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
The company's capital structure is sourced from internal and external, therefore the decision to fund the capital structure must be reviewed in-depth, and various impacts or risks that may affect the company that may occur in the future. One of the capital structure funding decisions made by the company is external capital structure funding. This study aims to analyze and empirically prove the stability of sales stability, information technology capital, and business risks to the company's policy of selecting an external capital structure funding model for manufacturing industry companies in Indonesia listed on the Indonesia Stock Exchange. This type of research is quantitative using secondary data, with the population in this research is all manufacturing industry companies listed on the Indonesia Stock Exchange which number 163 manufacturing industry companies. Sampling method in this study using purposive sampling method, with some criteria of sample withdrawal, the number of samples used as many as 32 manufacturing industry companies with observation data 160 financial statements. The data analysis technique used is multiple regression analysis. The results showed that: 1). Sales stability has a positive and significant impact on the company's policy of selecting an external capital structure funding model. 2). Information technology capital has a positive and significant impact on the company's policy of selecting an external capital structure funding model. 3). Business risk is insignificant and has no effect on the company's policy of selecting an external capital structure funding model.